The Influence of Business Owner Characteristics, Financial Literacy, and Financial Inclusion on Business Capital Choice Decision and its Implications for Business Growth - Yuszak Mahya; Nanny Dewi; Wiyas Yulias Hasbu (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the influence of business owner characteristics, financial literacy, and financial inclusion on capital structure decisions and their implications for business growth in Micro, Small, and Medium Enterprises (MSMEs). Using a quantitative approach, data were collected through questionnaires distributed to 208 MSME owners in the Jabodetabek area who are members of the Ilmukeuangan.com Alumni Community, selected through purposive sampling with criteria of having operated for at least one year. The research variables include entrepreneur characteristics, financial literacy, and financial inclusion as independent variables, capital structure as a mediating variable, and business growth as the dependent variable. Data analysis was conducted using Structural Equation Modeling (SEM) through SmartPLS 3.0. The results show that the research model has moderate predictive strength with R-Square values of 0.571 for business growth and 0.565 for capital structure, and a Goodness of Fit (GoF) value of 0.594 indicating a robust model. Of the six direct effect hypotheses tested, four were accepted and two were rejected. Financial literacy (T-stat: 5.421) and financial inclusion (T-stat: 9.452) significantly influence capital structure, while entrepreneur characteristics do not have a significant effect. For business growth, entrepreneur characteristics (T-stat: 7.725) and financial inclusion (T-stat: 3.759) show significant direct effects, but capital structure does not significantly influence business growth. The mediation test results indicate that capital structure significantly mediates the relationship between financial literacy and financial inclusion on business growth, but does not mediate the relationship between entrepreneur characteristics and business growth.